Analisis Perhitungan Gaya Internal Rangka Ruang dengan Menggunakan Metode Elemen Hingga - Widyawaty, Oktaviany; Husni, Hasti Riakara; Suyadi, Suyadi (Universitas Lampung, 2016)
The finite element method is a method of modelling of an object to divide into smaller parts as awhole still has the same properties as the whole thing before it was divides into smaller sections(discretization). The finite element method can be used to analyse various types of structures, suchas plane truss, space truss, plane frame, space frame, beam, and grid.The main difference space truss and space truss are the number of degrees of freedom at eachnode. Each bar in order to space has six degrees of freedom. A space truss structure formed by thecombination of elements order in XYZ space. Variations of incorporation requires thetransformation of the characteristic elements of the local coordinate system to the globalcoordinate system.In this study, analysis of space truss using the finite element method will be assisted with thesoftware Matlab. Where the result of Matlab will be compared with result from the SAP2000. Theresults of this analysis are joint displacement, joint reaction, and element forces.Keywords : Finite Element Method, Space Truss, Matlab